PELAKSANAAN PROMOSI MELALUI KEGIATAN EVENT LOMBA NON AKADEMIK TINGKAT SMP/MTS - Zulkipli Zulkipli; Ivan Riyadi; Afif Alfiyanto; Rudini Rudini; Mahin Ainun Naim (JURNAL PENDIDIKAN GLASSER, 2022)
School creativity in gathering the interest of registrants in each school is very much needed, including conducting non-academic competitions, as has been done by SMA Muhammadiyah 6 Palembang. The title of this study is "Implementation of Promotions Through Non-Academic Competition Events for Junior High School/Madrasah Tsanawiyah at Muhammadiyah 6 Senior High School Palembang". This study aimed to determine the implementation of promotion through non-academic competitions at the Junior High School/Madrasah Tsanawiyah at Muhammadiyah 6 Senior High School Palembang and supporting factors and obstacles to school promotion through non-academic competition events at the junior high school / MTs level at Muhammadiyah 6 Palembang High School. In this study, the type of research that will be used as a type of qualitative descriptive research. The primary informants in this study were the Principal, while the supporting informants were the Vice Principal for Student Affairs / Public Relations and Teachers of Muhammadiyah 6 Palembang High School. The data collection techniques used are observation, interviews and documentation. The analytical methods used are data reduction, data presentation and conclusion. The results of this study show that the Implementation of School Promotion through Non-Academic Competition Events at SMA Muhammadiyah 6 Palembang has been carried out well through several indicators, namely market, mission, message, media, money and measurement. The supporting factors and obstacles to school promotion through non-academic competition events at the junior high school / MTs level at Muhammadiyah 6 Palembang High School are 1) Supporting factors are good communication between student committees, teachers, staff and school stakeholders, facilities to support activities and the availability of sufficient funds so that the competition event is held properly. 2) The inhibiting factors are other schools that hold similar non-academic competition events and inadequate medical equipment so that injured students must be taken to the hospital when there are injured students.